2005
DOI: 10.1080/10799890500464704
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Celecoxib on Ca2+Fluxes and Proliferation in MDCK Renal Tubular Cells

Abstract: The effect of celecoxib on renal tubular cells is largely unexplored. In Madin Darby canine kidney (MDCK) cells, the effect of celecoxib on intracellular CaCa2+ concentration ([Ca2+]i) and proliferation was examined by using the Ca(2 +)-sensitive fluorescent dye fura-2 and the viability detecting fluorescent dye tetrazolium, respectively. Celecoxib (> or =1 micro M) caused an increase of [CaCa2+]i in a concentration-dependent manner. Celecoxib-induced [CaCa2+]i increase was partly reduced by removal of extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…The intracellular Ca 2+ store involved in methoxychlor‐induced [Ca 2+ ] i rise was explored. Previous studies have shown that the endoplasmic reticulum is the major Ca 2+ store in MDCK cells . Figure A shows that in Ca 2+ ‐free medium, addition of 20 μM methoxychlor induced a [Ca 2+ ] i rise of 35 ± 2 nM (n = 3).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The intracellular Ca 2+ store involved in methoxychlor‐induced [Ca 2+ ] i rise was explored. Previous studies have shown that the endoplasmic reticulum is the major Ca 2+ store in MDCK cells . Figure A shows that in Ca 2+ ‐free medium, addition of 20 μM methoxychlor induced a [Ca 2+ ] i rise of 35 ± 2 nM (n = 3).…”
Section: Resultsmentioning
confidence: 87%
“…The MDCK cell line is a useful model for renal research. It has been shown that in this cell type, several ligands can cause a [Ca 2+ ] i rise, such as sulforaphane , anandamide , celecoxib , and endogenous ligands like ATP and bradykinin , via causing Ca 2+ entry and Ca 2+ release.…”
mentioning
confidence: 99%
“…Ca 21 signaling plays a crucial role in the function of almost all cell types including MDCK renal tubular cells [Jan et al, 1998[Jan et al, , 2000Wang et al, 2005;Yeh et al, 2006;Liu et al, 2008]. A change in [Ca 21 ] i in renal tubular cells may affect many functions including cell volume regulation and transport [Vallon, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were performed to explore the Ca 21 entry pathway of the capsaicin-induced response. Three store-operated Ca 21 influx inhibitors, nifedipine, econczole, and SKF96365 [Harper et al, 2003;Ishikawa et al, 2003;Jiang et al, 2006;Quinn et al, 2004], the protein kinase C activator, phorbol Previous reports have shown that the endoplasmic reticulum is the major Ca 21 store in MDCK cells [Jan et al, 1998[Jan et al, , 2000Wang et al, 2005;Yeh et al, 2006;Liu et al, 2008]. Thapsigargin, an inhibitor of endoplasmic reticulum Ca 21 pumps [Thastrup et al, 1990], was used to deplete endoplasmic reticulum Ca 21 stores to see whether capsaicin utilized this store to cause intracellular Ca 21 release.…”
Section: Ca 21 Entry Pathways Of the Capsaicin-induced Responsementioning
confidence: 99%
“…The Madin Darby canine kidney (MDCK) (renal tubular) cell line is a useful model for renal research. It has been shown in this cell line that [Ca 2+ ] i increases in response to stimulation via exogenous ligands such as melittin [Liu et al, 2008], anandamide [Yeh et al, 2006], celecoxib [Wang et al, 2005], and endogenous ligands like ATP [Huang and Jan, 2001] and bradykinin [Jan et al, 2000]. In the present study, using fura‐2 as a fluorescent Ca 2+ ‐sensitive dye, we show that capsazepine induces concentration‐dependent [Ca 2+ ] i increases both in the presence and absence of extracellular Ca 2+ in MDCK cells.…”
Section: Introductionmentioning
confidence: 99%